Cryotherapy for trichiasis in ocular cicatricial pemphigoid. Issue 10 (October 1994) - Elder, M J; Bernauer, W
Abstract : Trichiasis is a common and potentially sight threatening complication of ocular cicatricial pemphigoid and is usually secondary to cicatricial entropion. This study aimed to assess the success and complications of eyelid cryotherapy for trichiasis in a group of patients with long term follow up. The case records of all patients with ocular cicatricial pemphigoid that attended the external disease clinic at Moorfields Eye Hospital from 1980 to 1992 were reviewed. Each eyelid was divided into three horizontal zones. Cryotherapy was delivered with an Amoilette cryoprobe for approximately 30 seconds. Failure of the cryotherapy was defined as a regrowth of the eyelashes within the treated zone that either required epilation for symptom control or caused keratopathy. Ninety two lid zones were treated, involving 25 lids of 12 patients. The cumulative chance of success decreased rapidly to 40% over the first year. Thereafter, the chance of success declined slowly to 34% at 4 years. Complications included lid notching (n = 2), tarsal atrophy (n = 1), altered lid contour (n = 1), and temporarily raised intraocular pressure (n = 1). All patients had quiescent disease at the time of the cryotherapy and no patients showed increased conjunctival disease activity after treatment. Six patients were taking systemic immunosuppression medication. When ocular cicatricial pemphigoid is quiescent, lid cryotherapy has an acceptable complication rate. The major reason for recurrence of the trichiasis was attributed to inadequate follicle freezing.